Power Up Your Profits: - Waugh, Troy (John Wiley & Sons, 2005)
This updated Second Edition demonstrates how combining the power of trust with the power of persuasion can help CPAs sell their services more effectively. Each chapter develops a key concept of marketing or selling that's easy to follow and shows how to apply the concepts to any CPA practice. Through a step-by-step approach to developing and mastering a stronger marketing and sales presence, this book focuses on how to dramatically enhance the reader's growth potential. It presents real-world examples from top CPA rainmakers and other marketing and management gurus, including Tom Peters. This updated second edition offers interviews covering Sarbanes-Oxley and the new accounting rules